Local Anesthetics and Antipsychotic Phenothiazines Interact Nonspecifically with Membranes and Inhibit Hexose Transporters in Yeast - Uesono, Yukifumi (Genetics, 2016)
Action mechanisms of anesthetics remain unclear because of difficulty in explaining how structurally different anesthetics cause similar effects. In Saccharomyces cerevisiae, local anesthetics and antipsychotic phenothiazines induced responses similar to those caused by glucose starvation, and they eventually inhibited cell growth. These drugs inhibited glucose uptake, but additional glucose conferred resistance to their effects; hence, the primary action of the drugs is to cause glucose starvation. In hxt(0) strains with all hexose transporter (HXT) genes deleted, a strain harboring a single copy of HXT1 (HXT1s) was more sensitive to tetracaine than a strain harboring multiple copies (HXT1m), which indicates that quantitative reduction of HXT1 increases tetracaine sensitivity. However, additional glucose rather than the overexpression of HXT1/2 conferred tetracaine resistance to wild-type yeast; therefore, Hxts that actively transport hexoses apparently confer tetracaine resistance. Additional glucose alleviated sensitivity to local anesthetics and phenothiazines in the HXT1m strain but not the HXT1s strain; thus, the glucose-induced effects required a certain amount of Hxt1. At low concentrations, fluorescent phenothiazines were distributed in various membranes. At higher concentrations, they destroyed the membranes and thereby delocalized Hxt1-GFP from the plasma membrane, similar to local anesthetics. These results suggest that the aforementioned drugs affect various membrane targets via nonspecific interactions with membranes. However, the drugs preferentially inhibit the function of abundant Hxts, resulting in glucose starvation. When Hxts are scarce, this preference is lost, thereby mitigating the alleviation by additional glucose. These results provide a mechanism that explains how different compounds induce similar effects based on lipid theory.